Интродукция видов рода Fraxinus в Донецком ботаническом саду НАН Украины - Терещенко, С.И. (Промышленная ботаника, 2002)
The results of introduction of twelve species and three forms the genus Fraxinus L. in the Donetsk botanical gardens, Nat. Acad. Sci. of Ukraine are stated. Their seasonal rhythm of development, peculiarities of growth, development and tolerance have been made. The assessment of the crop capacity and their being ornamental under the arid conditions of the Ukraine’s south-east have been performed. The most deserving species and forms, such as F. lanceolata Borkh., F. oxycarpa Willd., F. pensylvanica March., F. syriaca Boiss., F. tomentosa Michx., F. mandshurica Rupr., F. e. var. aurea Willd., F. e.var.globosa Hort., F. e. var. diversifolia (Ait.) Lingelsh. are recommended for the extensive use in the urban forestry of the Ukraine’s southeast.